1981
DOI: 10.1093/ajcn/34.8.1552
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol, coconuts, and diet on Polynesian atolls: a natural experiment: the Pukapuka and Tokelau Island studies

Abstract: Two populations of Polynesians living on atolls near the equator provide an opportunity to investigate the relative effects of saturated fat and dietary cholesterol in determining serum cholesterol levels. The habitual diets of the toll dwellers from both Pukapuka and Tokelau are high in saturated fat but low in dietary cholesterol and sucrose. Coconut is the chief source of energy for both groups. Tokelauans obtain a much higher percentage of energy from coconut than the Pukapukans, 63% compared with 34%, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 14 publications
0
45
0
4
Order By: Relevance
“…39 There is solid evidence of a change in diet among Pacific people following migration, with an increase in alcohol and tobacco consumption, meat, cereals, dairy and simple sugars. [40][41][42][43] It should be noted that these changes are not uniformly towards a greater CRC risk, e.g. increasing fibre.…”
Section: Cancer Prevention and Controlmentioning
confidence: 99%
“…39 There is solid evidence of a change in diet among Pacific people following migration, with an increase in alcohol and tobacco consumption, meat, cereals, dairy and simple sugars. [40][41][42][43] It should be noted that these changes are not uniformly towards a greater CRC risk, e.g. increasing fibre.…”
Section: Cancer Prevention and Controlmentioning
confidence: 99%
“…Australian Aborigines never developed agriculture [13]. The early settlers of the Nauru and other Pacific atolls consumed a diet dominated by fish and coconuts, i.e., low in carbohydrate and high in protein [22]. Attempts to cultivate root crops were thwarted by drought, barren soils and natural phenomena such as hurricanes.…”
Section: The Low-carbohydrate Existencementioning
confidence: 99%
“…Coconut oil contains mostly (>90%) of saturated fatty acids and it has received bad reputation to be hypercholesterolemic in action [2,3]. Clinical studies have revealed the consumption of coconut was not associated with cardiovascular disease and heart attacks [4]. Virgin coconut oil (VCO), which refers to coconut oil produced from coconut milk by natural or mechanical method (wet method).…”
Section: Introductionmentioning
confidence: 99%